Activation of GCN2/ATF4 signals in amygdalar PKC-δ neurons promotes WAT browning under leucine deprivation - Feixiang Yuan (Nature Portfolio, 2020)
The browning of white adipose tissue has potential benefits on metabolic disorders, but the nutritional factors and neuronal signals that mediate browning remain incompletely understood. Here, the authors show that leucine deprivation can induce WAT browning via GCN2/ATF4 signaling in amygdalar PKC-δ neurons.